Effects of water re-allocation in the Ebro river basin: A multiregional input-output and geographical analysis. (1st July 2019) - Almazán-Gómez, Miguel A.; Duarte, Rosa; Langarita, Raquel; Sánchez-Chóliz, Julio
Abstract: The quality and availability of water are affected by numerous variables, through which the evaluation of water uses from different perspectives, and policy proposals to save water have now become essential. This paper aims to study water use and the water footprint from a river basin perspective, taking into account regions, sectors, and municipalities, while considering the physical frontier along with the administrative sectors. To this end, we have constructed a multi-regional input-output table for the Ebro river basin, disaggregating the primary sector into 18 different crops and 6 livestock groups. We pay special attention to crop production because it is the most water-consuming industry. The construction of the multi-regional input-output model represents an important contribution to the literature, in itself, since, to the best of our knowledge, it is the first to be built for this large basin. We extend this multi-regional input-output model to assess the water footprint by sectors and regions within the basin. We use these data to propose two scenarios: reallocating final demand to reduce the blue water footprint (scenario 1), and increasing value added (scenario 2). These scenarios outline the opportunity costs of saving water in socioeconomic terms in the basin. In another application, we downscale the multi-regional input-output model results at the municipal level and depict them using a geographical information system, identifying the hotspots and the areas that would pay for the socioeconomic opportunity costs of saving water. Our results suggest that saving 1 hm 3 of blue water could cost around €41, 500 of value added if we consider the entire basin. However, this water re-allocation implies losses and gains at the municipal level: some municipalities would reduce value added by more than €30, 000, while others would gain more than €85, 000 of value added. These tools and results can be useful for policy makers when considering re-allocating water. The contribution and the novelty of this paper is the construction of the multiregional input-output model for the Ebro river basin, and its link with geographical systems analysis at the municipal level. Highlights: We have constructed a multi-regional input-output table for the Ebro river basin. We extend the model to assess the water footprint by sectors and regions. We develop a strategy to downscale the results at the municipal level. We evaluate the trade-off between saving water and value added. Using GIS software, we show the spatial distribution of the results.